Логики квазиарных предикатов первого порядка - Шкильняк, С.С. (Кибернетика и системный анализ, 2010)
Досліджуються композиційно-номінативні логіки квазіарних предикатів. Розглянуто спектр композиційно-номінативних логік, описано класи першопорядкових логік квазіарних предикатів. Для загального випадку логік квазіарних предикатів кванторного рівня побудовано числення секвенційного типу, доведені його коректність і повнота. Composition nominative logics of quasi-ary predicates are studied in the paper. The spectrum of composition nominative logics is considered and various classes of first-order logics of quasi-ary predicates are specified. Sequent calculi are constructed for the general case of logics of quasi-ary predicates of quantifier level, and soundness and completeness theorems are proved.